Corrigendum to “Non-thermal atmospheric-pressure plasma potentiates mesodermal differentiation of human induced pluripotent stem cells” [Heliyon 8(12) (December 2022) e12009] - Mime Kobayashi; Kiichiro Tomoda; Hirofumi Morihara; Michio Asahi; Tetsuji Shimizu; Shinya Kumagai (Heliyon, 2023)
[This corrects the article DOI: 10.1016/j.heliyon.2022.e12009.].